The relationship between monetary rewards and job satisfaction among administrative personnel at selected public schools in Setiu District, Terengganu / Arina Syazana Azmi - Azmi, Arina Syazana (Faculty of Business and Management, 2019)
The purpose of this study were to investigate the relationship between monetary rewards and job satisfaction as well as to examine the job satisfaction among administrative personnel at selected public schools in Setiu District. Terengganu. This study used disproportionate sampling technique and the response rate was 100.0%. The data were collected by using survey questionnaire distributed to the respondents (n=86) where they, had to rate their job satisfaction on monetary rewards (salary, bonuses and allowances). The questionnaire was adopted from Minnesota Satisfaction Questionnaire (1967) and Robles (2018), and the result was analyzed by using SPSS V-22. The respondents were from 7 primary and 6 secondary public schools and their grade of position were from N11 and N19. They have 10 to 15 years length of service and their salary were between RM2,001 to RM3,000. They have obtained 90 to 100 for their performance evaluation marks. The findings showed that there was very strong relationship between monetary rewards and job satisfaction (r=0.79, p=0.00). Moreover, they all had similar correlation between job satisfaction and salary (r=0.70, p=O.OO), bonuses (r=0.72, p=O.OO) as well as allowances (r=0.84, p=0.00). Obviously, administrative personnel in this study have moderate perception towards their job satisfaction. It is recommended that the top management increase the monetary rewards and provide more financial rewards. The researcher suggests that future study should cover other industries and includ a large number of respondents, in order to gain a comprehensive and reliable result of analysis.